Africa agriculture trade monitor 2023 - Odjo, Sunday P.; Traoré, Fousseini; Zaki, Chahir (AKADEMIYA2063, 2023)
The 2023 Africa Agriculture Trade Monitor, a flagship publication of AKADEMIYA2063 and the International Food Policy Research Institute, provides an overview of trade in agriculture in Africa, including analysis of short- and long-term trends and drivers behind Africa’s global trade, intra-African trade, and trade within Africa’s regional economic communities. The 2023 report highlights the growing treat of climate change to trade; looks closely at the impact of the Russia-Ukraine war on food security and poverty; draws on the report’s robust trade database to analyze African agrifood trade and nutrition; examines the types of trade agreements that successfully boost trade, and the implications for the African Continental Free Trade Area Agreement; and includes focused chapters on the competitiveness of cotton value chains in Africa and world trade and on trade integration in Economic Community of Central African States.